Experimental and numerical investigation of performance of an ethanol-gasoline dual-injection engine. (1st November 2019) - Zhuang, Yuan; Zhu, Guodong; Gong, Zhen; Wang, Chenfang; Huang, Yuhan
Abstract: Experiments and simulations were performed to investigate the effect of ethanol direct injection plus gasoline port injection (EDI + GPI) on engine performance. Gasoline direct injection plus GPI (GDI + GPI) was also tested as a reference to EDI + GPI. The experimental results showed that volumetric efficiency increased with the raise of direct injection ratio in both EDI + GPI and GDI + GPI conditions. The volumetric efficiency and IMEP of EDI + GPI were greater than that of GDI + GPI, due to the stronger charge cooling effect of EDI. Combustion process was improved by EDI when ethanol energy ratio (EER) was less than 42%, however further increase of EER led to the deterioration of combustion process. Simulation results showed that ethanol's high laminar flame speed played a dominate role to the improvement of combustion process. Although EDI negatively affected the equivalence ratio around spark plug, this disadvantage was offset by the high laminar flame speed of ethanol, resulting in shorter initial and major combustion durations. Simulation results also found that combustion process was deteriorated when EER was greater than 42%, which was mainly due to over-cooling and poor mixing of EDI. Regarding emissions, NO decreased while CO and HC increased with the raise of both EDI and GDI ratios. Highlights: EDI + GPI showed higher volumetric efficiency and IMEP than GDI + GPI did. EDI + GPI led to lower in-cylinder temperature and shorter combustion duration. Ethanol's high laminar flame speed was the main contributor to short combustion duration. HC and CO of EDI + GPI first decreased and then increased with the raise of ethanol ratio.